2022
DOI: 10.1002/1873-3468.14290
|View full text |Cite
|
Sign up to set email alerts
|

An endogenous bornavirus‐like nucleoprotein in miniopterid bats retains the RNA‐binding properties of the original viral protein

Abstract: Endogenous bornavirus-like nucleoprotein elements (EBLNs) are sequences derived from bornaviral N genes in vertebrate genomes. Some EBLNs have been suggested to encode functional proteins in host cells; however, little is known about their evolution and functional relationship to the viral genes from which EBLNs originate. Here, we predicted functionality of EBLNs based on the properties of N as an RNA-binding protein. We showed an EBLN in miniopterid bats (miEBLN-1) has evolved under purifying selection and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…We previously found miEBLN-1, which is derived from an ancient orthobornaviral N gene and retains the intact ORF, in miniopterid bats (Fig. 2a) and the miEBLN-1 "empty" loci in the genomes of Rhinolophus ferrumequinum and Phyllostomus hastatus [10]. To confirm these results, we reanalyzed the miEBLN-1 empty loci using the current genome datasets.…”
Section: Identification Of N/x/p Transcript-like Ebls In Miniopterid ...mentioning
confidence: 68%
See 2 more Smart Citations
“…We previously found miEBLN-1, which is derived from an ancient orthobornaviral N gene and retains the intact ORF, in miniopterid bats (Fig. 2a) and the miEBLN-1 "empty" loci in the genomes of Rhinolophus ferrumequinum and Phyllostomus hastatus [10]. To confirm these results, we reanalyzed the miEBLN-1 empty loci using the current genome datasets.…”
Section: Identification Of N/x/p Transcript-like Ebls In Miniopterid ...mentioning
confidence: 68%
“…We previously identified miEBLN-1, an EBLN derived from an ancient orthobornavirus that retains an intact N ORF in miniopterid bats [10]. The miEBLN-1 locus is present in the genomes of miniopterid bats, specifically in those of Miniopterus natalensis, M. schreibersii , and M. fuliginosus , but is empty (i.e., syntenic loci lacking miEBLN-1) in the genomes of Rhinolophus ferrumequinum and Phyllostomus hastatus .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in vivo experimental evidence for antiviral roles mediated by nrEVE-derived piRNAs against cognate viral replication was only revealed in Aedes aegypti ovaries 21 . In addition to the antiviral roles, functional studies of nrEVEs have mainly focused on coopted EBLNs in mammals [28][29][30][31] , whereas in vivo studies of the cellular functions of domesticated nrEVEs in arthropods are scarce. In this study, although the production of piRNAs was found for the majority of transcribed ToEVEs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…hsEBLN-2 was shown to be translated and encoded by a mitochondrial protein that is associated with cell viability, demonstrating the potential of co-opted mammalian function originating from ancient bornavirus infection 30 . Moreover, the EBLNs of miniopterid bats have been shown to encode an RNA-binding protein with biochemical properties similar to those of bornaviral nucleoprotein (N), suggesting that EBLNs can maintain the properties of their original genes 31 . In addition to EBLNs, a number of studies have shown that nrEVEs are also transcriptionally active, and several nrEVEs have maintained intact ORFs under strong purifying selection in invertebrates, mostly mosquitoes 7,32 .…”
mentioning
confidence: 99%